Application of Videoscribe Media to Cognitive Learning Outcomes in Social Science Learning at Madrasah Ibtidaiyah: Penerapan Media Videoscribe Terhadap Hasil Belajar Kognitif pada Pembelajaran Ilmu Pengetahuan Sosial di Madrasah Ibtidaiyah - Dewi, Nur Alfina; Afandi, Rifki (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose study are (1) to find out whether there was an effect of videoscribe learning media on social studies learning outcomes for grade 4 at MI Nurus syafi'I, (2) to find out how much influence videoscribe learning media had on social studies learning outcomes for grade 4 at MI Nurus syafi'i This study uses a quantitative experimental research design using the PreExperimental – One Group Pretest Posttest Design research design. The results showed that there was a positive and significant influence on the videoscribe learning media on the social studies learning outcomes of fourth grade students of MI Nurusyafi'I Gedangan, as evidenced by the t-count value of 10,947> 2,074, and the magnitude of the effect can be seen from Cohen's d calculations which show the result of 2.12 > 0 ,8 The conclusion of this study is that there are a major influence on student cognitive learning outcomes at MI Nurus Syafii.